Prevalence of Musculoskeletal Disorders among Recreational Cyclists - Manali K. Shah; Megha S. Sheth; Ruchi Desai (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background and Need of Study: Recreational cycling has been popular in India for a decade, so the number of patients presenting with musculoskeletal problems has also increased. There are only a few studies available focusing on finding musculoskeletal problems occurring in recreational cyclists in India. Thus, the objective of this study was to determine the prevalence of musculoskeletal discomforts (MSDs) in recreational cyclists. Methods: A cross-sectional survey of 110 recreational cyclists aged 18 years or more, for cycling at least 100 km/month and for 6 months or more from various cycling clubs and the community of Ahmedabad city was performed in this study using convenience sampling. Included subjects were interviewed personally by the team of trained physiotherapists and a questionnaire was filled. A descriptive analysis was conducted. Result: A total of 110 participants (84 males and 26 females) were interviewed for the survey. Their mean cycling duration, frequency, and volume were 41.1 ± 34.6 months, 2.3 ± 1.5 days/week, and 257.2 ± 252.5 km/month respectively. A total of 49.1% of cyclists reported the presence of MSDs, 62.9% reported the presence of pain at one anatomical site, and 37.1% reported pain at more than one site during cycling. The most common anatomical sites for MSD during cycling were knee (21.8%) followed by lower back (13.6%), upper back (9.1%), leg (8.2%), neck (7.3%), elbow (4.5%), and shoulder (3.6%). A total of 32.7% of cyclists reported discomfort persists even after cycling and about 10% reported that the above pain affects their day-to-day activities. Conclusion and Clinical Implications: This study found that MSDs are common in recreational cyclists, with knee and lower back most commonly involved. This data could provide the evidence required to find risk factors responsible for MSDs in cyclists and develop injury prevention and treatment plans for common MSDs seen in recreational cyclists.